The Theoretical Foundations of Psychological and Pedagogical Subjects Integration in the system of Teacher Training Education at the Turn of XIX-XX Centuries - E V Kondratenko (Peoples' Friendship University of Russia (RUDN University), 2011)
Scientifically valid synthesis of knowledge of the person as the subject of the pedagogical process is currently considered a controlling factor for the pedagogical education enhancement aimed at the development of system pedagogical thought of future teachers and the establishment of their professional competence. In this respect a special emphasis is laid on the historical background analysis of psychological and pedagogical disciplines integration within the system of pedagogical training in Russia.